Using OSM, Geo-Tagged FLICKR Photos and Authoritative Data: A Quality Perspective - Antoniou, Vyron (2016)
The appearance of OpenStreetMap (OSM) in 2004 sparked a phenomenon known as Volunteered Geographic Information (VGI). Today, VGI comes in many flavours (e.g. toponyms, GPS tracks, geo-tagged photos, micro-blogging or complete topographic maps) and from various sources. One subject that has attracted research interest from the early days of VGI is how good such datasets are and how to combine them with authoritative datasets. To this end, the paper explores three intertwined subjects from a quality point of view First, we examine the topo-semantic consistency of OSM data by evaluating a number of rules between polygonal and linear features and then paying special attention to quality of Points of Interest (POIs). A number of topo-semantic rules will be used to evaluate the valididy of features’ location. The focus then turns to the use of geo-tagged photos to evaluate the location and type of OSM data and to disambiguate topological issues that arise when different OSM layers overlap.